2018
DOI: 10.3390/ijerph15102062
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions about the Federally Mandated Smoke-Free Housing Policy among Residents Living in Public Housing in New York City

Abstract: Background: To assess residents’ attitudes towards the United States (U.S.) Department of Housing and Urban Development’s new smoke-free public housing policy, perceptions about barriers to policy implementation, and suggestions for optimizing implementation. Methods: In 2017, we conducted 10 focus groups among 91 residents (smokers and nonsmokers) living in New York City public housing. Results: Smokers and nonsmokers expressed skepticism about the public housing authority’s capacity to enforce the policy due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…These findings are consistent with prior research showing individual-level rule support, especially among non-smokers [27][28][29]. Past research suggests that most of the support is driven by perceived health benefits of the rule [30]. However, despite the support and perceived benefits, there are consistent compliance barriers or resistance making enforcement a challenge for smoking-free rules no matter the geographic location or setting [8,9,27,[30][31][32][33][34].…”
Section: Individualsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are consistent with prior research showing individual-level rule support, especially among non-smokers [27][28][29]. Past research suggests that most of the support is driven by perceived health benefits of the rule [30]. However, despite the support and perceived benefits, there are consistent compliance barriers or resistance making enforcement a challenge for smoking-free rules no matter the geographic location or setting [8,9,27,[30][31][32][33][34].…”
Section: Individualsupporting
confidence: 88%
“…Past research suggests that most of the support is driven by perceived health benefits of the rule [30]. However, despite the support and perceived benefits, there are consistent compliance barriers or resistance making enforcement a challenge for smoking-free rules no matter the geographic location or setting [8,9,27,[30][31][32][33][34]. Studies show resident support for smoke-free multi-unit housing policies [3,8,35,36], including racially and ethnically diverse, low-income seniors [37], and property managers [3,8,38], although important differences existed by smoking status [39].…”
Section: Individualmentioning
confidence: 99%
“…Our findings substantiate published qualitative findings from focus groups where public housing residents reported pervasive marijuana use in their building's common areas. 22 Current non-smoking residents in our sample were also more sensitive to noticing, or at least reporting, pervasive marijuana use in their buildings. Overall, the widespread prevalence of SHMS exposure in MUH is especially concerning given an emerging body of evidence associating SHMS with poor health outcomes.…”
Section: Discussionmentioning
confidence: 74%
“…In general, study results are consistent with evaluations of tobacco policies in public or multi-person housing prior to the nationwide HUD rule. Specifically: a) residents have good knowledge, and are supportive, of the policy, especially non-smokers ( Kennedy et al, 2015 , Rokicki et al, 2016 ); b) residents are concerned that there isn’t enough enforcement ( Hernandez et al, 2019 , Jiang et al, 2018 , Kennedy et al, 2015 ); c) tobacco policies reduce, but do not eliminate self-reported smoking exposure in the building ( Hernandez et al, 2019 , Pizacani et al, 2012 , Rokicki et al, 2016 ); and d) the policy motivates smokers to make positive changes in their tobacco use ( Rokicki et al, 2016 ). Regarding quitting, Pizacani et al (2012) reported a higher policy associated quit rate (14.6%) than in this study (6.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, residents were knowledgeable of the smoke-free policy and supportive of it ( Kennedy et al, 2015 , Rokicki et al, 2016 ), with non-smokers more supportive than smokers ( Kennedy et al, 2015 ). However, enforcement of the policy was a concern, with some evidence that such enforcement was poor ( Hernandez et al, 2019 , Jiang et al, 2018 , Kennedy et al, 2015 ). Consistent with these concerns, evaluations of these smoke-free housing policies documented reductions, but not elimination, of smoking within the buildings ( Hernandez et al, 2019 , Pizacani et al, 2012 , Rokicki et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%